Intelligent Communication using Dynamic Scheduling Algorithm with Resource Allocation Scheme in VANETs Environments - Habelalmateen, Mohammed Ihsan; Abdalhussan Shalal, Azhaar; J, Suganya; Aljawaheri, Karar; Alsalamy, Fatima H.; Ahmed Alabboodi, Ahmed (Communications and Signal Processing, International Conference on, 2025)
Vehicular Ad hoc Networks (VANETs) are highly emerged nowadays and it occupies the top applications. During data transmission in VANETs due to high density and high-speed certain drawbacks will occur such as high congestion, high power utility and delay and as well that leads to affect the communication quality of the system. Achieving stable communication in high-speed vehicles are still a challenging problem. For that purpose, in this paper Intelligent Communication using Dynamic Scheduling Algorithm with Resource Allocation Scheme (IDSRA-VANETs) is proposed which mainly concentrates on dynamic scheduling and resource allocation. Through this process the vehicles are equipped with required resource to perform communication between one another. The transmission among the vehicles is properly scheduled according to the time slots which lead to attain stable and highly qualified communication. The results from the NS2 experimental demonstration proves that the proposed IDSRA-VANETs attains 10% higher delivery ratio, 40 sec lower delay, 300 packets lower routing overhead and 20% high efficiency.